Dermatofibrosarcoma protuberans (DFSP) successfully treated with sorafenib: case report - Kamar, Francois G (BioMed Central, 2013)
DFSP is a locally invasive, slow-growing tumor of the subcutaneous tissue that rarely metastasizes but recurs frequently after surgical excision. We report herein a case of highly recurrent, locally invasive DFSP that failed both postoperative radiation therapy and complete trial of Imatinib, but was successfully treated with Sorafenib, which showed unprecedented response.